Portuguese Recommendations for the management of Raynaud’s phenomenon and digital ulcers in systemic sclerosis and other connective tissue diseases - Santiago, T. (2024)
Objective: To develop evidence-based recommendations for the non-pharmacological and pharmacological management of Raynaud’s phenomenon (RP) and digital ulcers (DUs) in patients with systemic sclerosis and other im-mune-mediated connective tissue diseases (CTDs). Methods: A task force comprising 21 rheumatologists, 2 surgeons (vascular and plastic), 2 nurses, and 1 patient representative was established. Following a systematic literature review performed to inform the recommendations, statements were formulated and discussed during two meetings (one online and one in-person). Levels of evidence, grades of recommendation (GoR), and level of agreement (LoA) were determined. Results: Five overarching principles and 13 recommendations were developed. GoR ranged from A to D. The mean ± standard difference (SD) LoA with the overarching principles and recommendations ranged from 7.8±2.1 to 9.8±0.4. Briefly, the management of RP and DUs in patients with CTDs should be coordinated by a multidisci-plinary team and based on shared decisions with patients. Nifedipine should be used as first-line therapy for RP and/ or DUs. Sildenafil, tadalafil, and/or iloprost IV are second-line options for severe and/or refractory patients with RP and/or DUs. Sildenafil, tadalafil and/or Iloprost IV, should be prescribed for healing and prevention (also including bosentan) of DUs. In patients with RP and/or DUs, non-pharmacological interventions might be considered as add-ons, but there is limited quality and quantity of scientific evidence supporting their use. Conclusions: These recommendations will inform rheumatologists, specialist nurses, other healthcare profession-als, and patients about a comprehensive and personalized management of RP and DUs. A research agenda was developed to address unmet needs, particularly for non-pharmacologic interventions.